Pilihan Rasional Strategi Usaha Penjual Makanan Tradisional Dumbleg Khas Nganjuk - Cindy Olga Juanita; Waskito Waskito (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Traditional dumbleg food is increasingly threatened with extinction due to the regeneration of business actors and changes in public consumption patterns due to globalization. This study aims to analyze the business strategies applied by traditional dumbleg food sellers in maintaining their existence amid the growing culinary competition. This study uses a qualitative approach with a narrative research design. This research uses James S. Coleman's Rational Choice Theory and the methods used are observation, interviews and documentation. The main subjects in this study were 3 traditional dumbleg food sellers, 4 community members and 3 young people who were selected using purposive sampling technique. The results showed that there are two strategies used by traditional dumbleg food sellers in maintaining their business, namely conventional strategies and modern strategies. Conventional strategies such as offline marketing at Gondang Market, Rejoso Market and Nganjuk Square and marketing through bazaars at certain events. Meanwhile, modern strategies are carried out by marketing through digital platforms such as WhatsApp and Facebook as well as flavor innovations in products in order to reach a wider market and attract public interest. The combination of the two strategies can help increase the competitiveness of dumbleg food in the face of current culinary competition. The implication of this research is the importance of innovation in business strategies to be able to maintain the existence of traditional food.